(untitled) (Web of Teachers: Inderscience Research, 2026)
This article examines the problem of the spread of fake news in the modern digital media space, as well as the role and responsibility of bloggers from a scientific and theoretical point of view. The rapid dissemination of information through social networks makes bloggers key subjects of influence on public opinion. However, insufficient mechanisms for verifying information, personal interests and the desire for sensationalism contribute to the spread of false reports. The article highlights the issues of information reliability, ethical standards and legal responsibility of bloggers, and also emphasizes the importance of their role in countering fake news.